Analysis of the Competitive Advantage of SMEs During the Covid-19 Pandemic - Sonia Okky Astiti; Budi Rahardjo (Jurnal Fokus Manajemen, 2022)
The Covid-19 pandemic has caused Indonesia's economy to deteriorate since 2020. To deal with the economic crisis due to the impact of the pandemic, every UMKM need to know their competitive advantage. Competitive advantage is used by companies to compete with each other by managing their resources and capabilities. This research is a type of qualitative descriptive research using VRIO (Value, Rarity, Imitability, and Organization) analysis techniques. The purpose of this research is to find out the internal condition of a company, in this case it is UMKM Bintang Mahkota Convection in the face of the Covid-19 pandemic. The results showed that Bintang Mahkota Konveksi has internal resources in the form of tangible and intangible companies. UMKM Bintang Mahkota Konveksi can maintain and develop its resources and capabilities in the form of modern technology, strategic business locations, extensive warehouses, strong relationships with suppliers, experienced employees, and the skills to build relationships with suppliers in order to survive the Covid-19 pandemic.